LEGAL REGULATION OF THE EXAMINATION OF LAW DRAFTS - Zhamaladen Ibrahimovic, Ибрагимов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article is devoted to actual problems of the examination of law drafts. The article also noted insufficient knowledge about the scope of the examination of legislative activity. The author pays attention of researchers to improve expert activity in the legislative process.